2022
DOI: 10.1038/s41598-022-19552-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic study in piezo degradation of methylene blue by SbSI/Sb2S3 nanocomposites stimulated by zirconium oxide balls

Abstract: Mechanical energy harvesting by piezoelectric materials to drive catalysis reactions received extensive attention for environmental remediation. In this work, SbSI/Sb2S3 nanocomposites were synthesized as a catalyst. ZrO2 balls were used as an alternative mechanical force to ultrasonic for stimulating the piezocatalyst for the first time. The kinetics and thermodynamics of the piezo degradation of methylene blue (MB) were studied deeply. Besides the effect of the type of mechanical force, the number of ZrO2 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…The kinetics of piezo-desulfurization and characteristic constants of sulfur removal by piezocatalyst can be studied through kinetic measurements using pseudo-first-order, pseudo-second-order, and intra-particle diffusion. The Lagergren pseudo-first-order model is given as follows 26 , 40 :
Figure 11 ( a ) piezo-desulfurization rates over time for 500 ppm TP in different temperatures in presence of d2 as catalyst, ( b ) piezo-desulfurization rates over time for 500 ppm TP without using catalyst, ( c ) Pseudo-first-order and pseudo-second-order fitting for piezo-removal of TP in different temperatures, ( d ) Activation energy for removal of TP by piezo catalyst based on Arrhenius equation.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics of piezo-desulfurization and characteristic constants of sulfur removal by piezocatalyst can be studied through kinetic measurements using pseudo-first-order, pseudo-second-order, and intra-particle diffusion. The Lagergren pseudo-first-order model is given as follows 26 , 40 :
Figure 11 ( a ) piezo-desulfurization rates over time for 500 ppm TP in different temperatures in presence of d2 as catalyst, ( b ) piezo-desulfurization rates over time for 500 ppm TP without using catalyst, ( c ) Pseudo-first-order and pseudo-second-order fitting for piezo-removal of TP in different temperatures, ( d ) Activation energy for removal of TP by piezo catalyst based on Arrhenius equation.
…”
Section: Resultsmentioning
confidence: 99%
“…Pseudo-second-order kinetic model assumes that the rate of degradation is second order 26 , 41 , 42 . where k 2 is the pseudo-second-order rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…Further, these electrons react with the MB molecules, leading to the generation of reactive oxygen species (ROS), such as hydroxyl radicals (•OH). These ROS are highly reactive and oxidize the MB molecules, leading to their degradation into smaller molecules . The combination of high-energy electrons and ROS ensures that all MB molecules are degraded, leading to a 100% degradation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…As the ultrasonic power increases, the temperature of the reaction will also rise. Our previous study showed that increasing temperature resulted in a decrease in decontamination yield because dye degradation by piezo is exothermic 43 .…”
Section: Resultsmentioning
confidence: 99%